2019
DOI: 10.12688/wellcomeopenres.15042.1
|View full text |Cite
|
Sign up to set email alerts
|

Poor communication by health care professionals may lead to life-threatening complications: examples from two case reports

Abstract: We report two cases which highlight the fact how poor communication leads to dangerously poor health outcome. We present the case of a 50-year-old woman recently diagnosed with rheumatoid arthritis from Southern Nepal presented to Patan hospital with multiple episodes of vomiting and oral ulcers following the intake of methotrexate every day for 11 days, who was managed in the intensive care unit. Similarly, we present a 40-year-old man with ileo-caecal tuberculosis who was prescribed with anti-tubercular ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 5 publications
4
34
0
3
Order By: Relevance
“…Poor [27,30]. This finding is consistent with literature [45,46]. Thus, the need for continuous education from qualified health professionals cannot be overemphasized based on these findings.…”
Section: Discussionsupporting
confidence: 87%
“…Poor [27,30]. This finding is consistent with literature [45,46]. Thus, the need for continuous education from qualified health professionals cannot be overemphasized based on these findings.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our findings, previous studies found that the environment of ICU is very hostile for staff and the vulnerable critically ill elderly patients in terms of physical and mental stressors [27], [28], [29], [30]. In particular, the intensive care setting can be an obstacle to providing intensive care for long-stay elderly patients who have complex vital conditions [31].…”
Section: Discussionsupporting
confidence: 86%
“…In our case, the lack of proper communication between involved hospitals and doctors might be one of the reasons for his loss to follow-up [ 18 , 19 ]. Besides his financial constraints and ignorance, inadequate counselling about the diagnosis may have led to the discontinuity of care, which is very common in developing countries [ 18 , 19 ]. Due to limited resources in hospitals, it is common in developing countries to refer patients to other centers for further care [ 20 ].…”
Section: Discussionmentioning
confidence: 99%